2016
DOI: 10.1177/1043659616657877
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Mutuality, Filial Piety, and Depression in Family Caregivers in China

Abstract: Higher mutuality and stronger filial attitudes were significantly associated with less caregiver depression after the covariates were controlled. Mutuality explained 5.5% (p < .01) and filial attitude explained 4.6% (p < .01) of the variance in caregiver depression. Conclusion Mutuality and filial attitude may be protective factors against caregiver depression. Implications for Practice Supportive strategies can be implemented to enhance mutuality and filial attitude.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 36 publications
(76 reference statements)
3
30
1
Order By: Relevance
“…Numbers of studies have found that filial piety was closely associated with subjective happiness, depression, and life satisfaction (37)(38)(39). The result of the present study is in line with the expectations, and evidence suggests only children's visits, not "being married and living with the spouse," can predict the cognitive decline in older adults.…”
Section: Discussionsupporting
confidence: 88%
“…Numbers of studies have found that filial piety was closely associated with subjective happiness, depression, and life satisfaction (37)(38)(39). The result of the present study is in line with the expectations, and evidence suggests only children's visits, not "being married and living with the spouse," can predict the cognitive decline in older adults.…”
Section: Discussionsupporting
confidence: 88%
“…Depression may also be related to the functional dependence of stroke survivors which concurred with Lau et al. 's () Chinese family caregivers of stroke survivors in Hong Kong and Pan, Jones, and Winslow's () study of stroke caregivers in southern China. However, as caregiving burden decreased over time, caregivers’ depressive symptoms also decreased, which was consistent with a study conducted in Mainland China (Qiu & Li, ).…”
Section: Discussionsupporting
confidence: 79%
“…Despite the progression in using diverse tailoring strategies and increasing the aspects of interventions to be tailored, we found that most of the efforts have targeted surface-level rather than deep-level structures. Surface-level adaptations 91 refer to matching intervention materials and messages to the observable characteristics of the target population, whereas deep-level adaptations 91 [93][94][95][96] However, other studies found that a stronger sense of filial responsibility among Chinese caregivers was associated with more depressive symptoms. 97 Future interventions should consider these divergent findings and provide support in ways that align with how individual caregivers endorse and practice these Chinese traditional values in relation to their physical and mental wellbeing.…”
Section: Discussionmentioning
confidence: 99%